Architecture and society: some lessons on Muslim architecture from India - Spahic, Omer (IIUM Press, 2015)
This book deals with the subject of the relationship between Muslim architecture and society and how they influence each other, taking some social and historical segments of complex Indian society as a case study. The book consists of three independent studies which cover three vital aspects of Muslim architecture, especially in India: 1) Converting Hindu temples into mosques; 2) The royal funerary architecture of the Mughals; 3) The social significance of Mr. Nazeer Khan’s architecture. The lessons on Muslim architecture as derived from these three studies are by no means exhaustive. So complex and splendid is the realm of Muslim architecture, on the one hand, and so rich and diverse is the Muslim architectural legacy in India, on the other, to be adequately abridged in as little as three research papers. Besides, this book never attempted to do that. The book aims to reflect only on the three mentioned aspects, emphasizing in the process some notable at once spiritual and social qualities of Muslim architecture in general and in India in particular. The lessons expounded in the book revolve around the universal, fluid, multi-dimensional and value-loaded character of Muslim architecture that always eventually comes to the fore in any given socio-economic, religious and cultural context. Genuine Muslim architecture is thus understood as a type of architecture whose functions and, to a lesser extent, form are inspired primarily by Islam. Muslim architecture is a framework for the implementation of Islam. As such, it facilitates, fosters and stimulates the ‘ibadah (worship) activities of Muslims, which, in turn, account for every moment of their earthly lives. Muslim architecture can only come into existence under the aegis of the Islamic perceptions of God, man, nature, life, death and the Hereafter. Thus, authentic Muslim architecture would be the facilities and at the same time a physical locus of the actualization of the Islamic message. Practically, Muslim architecture represents the religion of Islam that has been translated into reality at the hands of Muslims. It also represents the identity of Islamic culture and civilization. The book shows how profound is the relationship between genuine Muslim architecture and a society where it is conceived, produced and utilized. This is so because Muslim architecture signifies a long process where all phases and aspects are equally important. The Muslim architecture process starts with having a proper understanding and vision which leads to making a right intention. It continues with the planning, designing and building stages, and ends with attaining the net results and how people make use of and benefit from them. Muslim architecture is a fine blend of all these factors which are interwoven with the treads of the belief system, teachings and values of Islam. Similarly, integral to the architectural processes are also local customs, traditions, geography and other numerous socio-economic considerations. Thus, the multi-tiered realm of architecture is not to be viewed only through the lens of architecture as pure art, science and technology. Rather, it is to be expanded into the higher and more sophisticated realms of existence. Existence, on the other hand, is not to be distorted or narrowed down, so as to go well with the corporeal ingredients and dimensions of architecture only. The orb of architecture, it follows, is to become known as an ultimate spiritualized and “supernatural” orb, whereas the life phenomenon is not to be mechanized or rendered merely physical, inconsequential and perfunctory just on account of some of us falling short of penetrating into its complex meanings and secrets. Architecture is synonymous with physical and spiritual flawlessness, precision and balance. It follows the rules and principles of the perfect universe designed and created by the Perfect Creator. It is a recognition, extension and augmentation of the faultless equilibrium that runs through the veins of total existence. By no means is it imitating, much less challenging or surpassing, the latter. Indeed, there can be no imitation or challenge between two completely different domains with different existential qualities and spheres of influence. God is the greatest and best Creator. Everything else comes second. Everything else, furthermore, ought to humble itself and subdue its existence to the paradigms of God’s revealed Words, mercy and grace. Architecture, it follows, is an act of at once humbleness, appreciation and veneration. Hence, practicing architecture denotes an opportunity to acknowledge and bring closer to the human grasp some of the greatest secrets of the universe. Architecture in many ways is a microcosm of the quintessence of the universe whereby architects, builders, artists, as well as the users of buildings, enjoy the prospects of engendering genuinely intimate relationships with the truth and its copious expressions and ways. It goes without saying that the thrust of the job of talented architects and artists is to feel indebted to God for the gifts and, as a way of appreciation, to remain humble, accountable and committed to enabling the ordinary people to experience and value those ontological truths as embodied by the art and architecture realms. Being an architect, therefore, is at once a privilege and responsibility, definitely the latter out-weighing the former. Architects are servants rather than masters. True architects are the servants of the dignified purpose of their profession, as well as of the needs and anticipations of people. At the same time, they are visionaries on account of their exceptional abilities and flair, inspiring and guiding those around them and making their lives more exciting, delightful and consequential. Architecture, therefore, is not just a profession. It is a life to be lived delightfully and responsibly. Successfully researching in India about the themes of the book was possible only because of the unreserved, kindest and heart-felt support, help and hospitality of many people in the Indian states of Kerala, Uttar Pradesh, Gujarat and New Delhi. I hereby reserve special thanks and praise for Mr. Nazeer Khan, his wonderful family and his clients in India and abroad, Mr. Umer Melmuri, Mr. Abbas Panakkal, Mr. Naufel and Dr. Hussain Randathani and their respective families, Sayyid Ibrahim al-Khalil al-Bukhari, the Chairman of the Academy of Ma’din al-Thaqafah al-Islamiyyah in Malappuram in Kerala, and for all staff and students of the same Academy. Also, I feel very much indebted to Mr. Adam Ghanchi, Mr. Yusuf Yakub Patel and Mr. Hanif Sanghariyat and their families who made my visit and stay in the Gujarat state extremely enjoyable and home-like. It was due to all of them that my visits to India were memorable. I will cherish those wonderful memories forever. Thus, I pray to Almighty God to grant all the persons mentioned above the best in this world and the hereafter. Finally, I welcome any constructive, academic suggestions concerning the book’s contents, my methodology, arguments, inferences, and my understanding and interpretation of the collected data.